CD4 and CD8 T Cell Memory Interactions Alter Innate Immunity and Organ Injury in the CLP Sepsis Model - Taylor, Matthew D.; Fernandes, Tiago D.; Kelly, Alexander P.; Abraham, Mabel N.; Deutschman, Clifford S. (Frontiers in Immunology, 2020)
The role of T cell memory in sepsis is poorly understood. Recent work has demonstrated that mice exposed to frequent antigenic stimulation, in contrast to laboratory mice, better recapitulate the human T cell repertoire. This difference may profoundly alter responses to inflammatory insults. We induced isolated T cell memory by inoculating C57Bl/6 mice with an anti-CD3 activating antibody, a process we term “immune education.” These mice were subjected to the cecal ligation and puncture (CLP) model of sepsis and responses were compared to those of isotype-treated controls. CLP-induced increases in 1) CD4 T cell production and serum levels of IFNgamma, 2) CD8 T cell granzyme B levels, and 3) innate cell function were all more pronounced in educated mice than in control mice. Immune education increased CLP-induced liver injury and decreased survival. The differences in responses to CLP were not recapitulated in mice with either isolated CD4 or isolated CD8 T cell memory. Relative to controls, CLP in educated CD8-/- mice (isolated CD4 memory) increased monocyte-derived dendritic cells. Combined CD4 and CD8 memory did not increase monocyte-derived dendritic cells; this combination recapitulated increases in neutrophil and inflammatory monocyte numbers in educated wild-type mice. Induction of T cell memory prior to CLP alters immune responses, organ function, and survival. Both CD4 and CD8 memory T cells play important and independent roles in this response. These findings have profound implications for the development of murine models of human inflammatory disorders such as infection and sepsis.